COL4A1 mutation in an Indian child presenting as ‘Cerebral Palsy’ mimic - Shah, Siddharth M; Patel, Drushi D (Indian Journal of Radiology and Imaging, 2020)
The COL4A1 gene (COL4A1) plays an important role in vascular basement membrane function and pathogenic mutations have been reported in mice and humans. The gene is expressed mainly in the human brain, eyes and kidneys. Pathogenic mutations result in a vast array of manifestations that can present throughout life including the foetal period. We present a case of an 11-year-old girl with right hemiparesis, congenital cataracts, epilepsy and magnetic resonance imaging (MRI) brain findings with a pathogenic COL4A1 mutation. Many of her clinical features are similar to those of a non-genetic cause of cerebral palsy highlighting the difficulties and delays in making this genetic diagnosis.
Keywords: Cerebral palsy; COL4A1 gene mutation; epilepsy; gliosis; magnetic resonance imaging; paediatric congenital cataract